(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study explores education’s contribution to Rwanda’s population growth and its determinants, such as fertility, mortality, and migration. Design/ Methodology/ Approach: The study uses secondary data from 2005 to 2020 sourced from databases of the World Bank, the United Nations, and the National Institute of Statistics of Rwanda. Specifically, quantitative research methodologies are used, including descriptive analysis, correlations, visualisations, multiple and multivariate linear regression, correlation, and comparative study, alongside econometric analysis such as multicollinearity, normality, and heteroscedasticity tests to ensure the quality, validity, and reliability of the results. Research Limitation: While the study utilises advanced statistical methods, the findings may not be fully generalisable across all contexts, particularly if the sample does not represent the broader population. Findings: Results indicate a statistically significant negative relationship between expenditure on education and population growth rate with (correlation is -0.896, regression coefficient is -0.298, R2 is 0.8846, p-value is 0.000). A unit increase in education expenditure reduces the population growth rate by 0.298. The R2 of 0.8846 suggests that 88.46% of the model is well explained. Additionally, spending on education shows a negative association with the total fertility rate (coefficient is -1.101, p-value is 0.000) and the Crude death rate (coefficient is -58.446, p-value is 0.000), indicating that higher education expenditure reduces fertility and mortality. However, there is no significant relationship between net migration (coefficient is 1.009, p-value is 0.109). Practical Implications: This study contributes to understanding the relationship between education and population growth rate in Rwanda, offering insights for policy interventions to control population growth. Social Implications: We recommend target policy interventions, such as increasing investment in education and addressing regional and gender disparities by focusing on areas with such cases. This controls fertility and mortality rates while also slowing long-term population growth. Originality/ Value: This study addresses the knowledge gap by examining how education impacts population growth rates. It provides empirical evidence and an econometric model to help policymakers use education to manage and predict future population dynamics.